Preparation and application of amorphous manganese dioxide nanoparticles and supercapacitor
By preparing a composite material of amorphous manganese dioxide nanoparticles and conductive carbon black and carbon nanotubes, the problem of poor conductivity of MnO2 electrodes is solved, high capacitance and good rate performance of high load electrodes are achieved, and high energy density storage is met Energy equipment requirements.
Patent Information
- Application Number
- CN202411599819.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The poor conductivity of existing MnO2 electrodes leads to blockage of charge transfer paths, resulting in low capacitance and severe attenuation at high current density, making it difficult to meet the needs of high-load energy storage equipment.
By preparing amorphous manganese dioxide nanoparticles and mixing them with conductive carbon black and carbon nanotubes, MnO2/CCB/CNTs composite materials are formed to improve the conductivity and electrochemical reaction rate of the electrode.
The high capacitance and good rate performance of high load MnO2 electrodes were achieved, with capacitance reaching 196.3F·g-1, surface energy density is 780.3μWh·cm-2, weight energy density is 34.3W·h·kg-1, and Maintained 98.2% cycle stability.
Smart Images

Figure CN119461488A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an electrode active material, and in particular to the preparation and application of amorphous manganese dioxide nanoparticles and a supercapacitor. Background Art
[0002] Supercapacitors are considered to be a promising candidate energy storage device due to their high power density, high safety and ultra-long service life. Active materials are the key factor affecting the electrochemical performance of supercapacitors.
[0003] Manganese dioxide (MnO2) has a high theoretical capacitance (1370F·g -1 ), long cycle stability and non-toxicity have attracted strong attention in the field of energy storage and have shown great application prospects. MnO2 has good tunnel structure, layered structure and three-dimensional space structure, and is widely used as an active material for supercapacitors, zinc-ion batteries, sodium-ion batteries, etc. Due to its multiple energy storage mechanisms, including electric double layer capacitance (EDLC), surface redox mechanism, ion insertion-deinsertion mechanism and charge compensation mechanism, MnO2-based electrodes exhibit ideal electrochemical behaviors, including ultra-high charge and discharge efficiency, high power / energy density and good cycle stability.
[0004] However, the capacitance of MnO2 electrodes is typically only 20%-30% of their theoretical capacitance due to the poor intrinsic conductivity of MnO2, which results in a blocked charge transfer path. Specifically, the excess charge generated by the electrochemical reaction hinders subsequent electrochemical reactions, resulting in a lower capacitance generated by the surface redox mechanism. To address this problem, the overall conductivity can be improved by combining MnO2 with a conductive matrix. However, this approach does not provide a significant improvement because the intrinsic conductivity is unchanged and substantial improvements are difficult to make. Therefore, new methods for designing highly active MnO2 structures are needed to increase the content of active ingredients.
[0005] A direct way to increase the active ingredient content in MnO2 electrodes is to reduce the crystal size to increase the exposed units (MnO6 octahedra), which enhances both the double layer capacitance component and the surface redox component due to the increased specific surface area (SSA). However, a high specific surface area inevitably leads to poor conductivity because its crystal structure is destroyed. Therefore, MnO2 electrodes with high specific surface area usually produce high capacitance at very low charge and discharge rates, but the capacitance decays severely with increasing current density. This decay can be effectively limited by reducing the mass loading of MnO2, not because of improved performance, but due to the simultaneous shortening of the charge / ion transfer path. Undoubtedly, ultra-low mass loading MnO2 electrodes will achieve sufficient charge transfer and fast ion transfer, resulting in a low dead volume content, which occupies space and weight in the electrode but provides little capacitance. However, this is meaningless for practical applications. For commercial purposes, the mass loading of active materials should be high enough (>10 mg cm -2 ), which will significantly improve the weight / volume performance of devices based on the overall weight because the amount ratio of current collector, electrolyte and packaging is reduced to a minimum. It is worth noting that for high-loaded MnO2 electrodes, the capacitance of MnO2 far away from the current collector is usually not able to be exerted due to the excess charge generated by the electrochemical reaction. At the same time, due to the lack of contact with the electrolyte for a large amount of active materials, the MnO2 close to the current collector cannot be activated. Therefore, a large amount of dead volume is generated in the high-loaded MnO2 electrode due to poor conductivity and poor ion transfer ability. Based on this result, the design of high-loaded MnO2 electrodes should consider fully activated MnO2 and criss-crossed conductive paths, which can not only provide sufficient active components, but also provide rich charge / ion transfer paths, thereby improving the electrochemical performance. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a method for preparing amorphous manganese dioxide nanoparticles, solving the problem of how to prepare ultrafine amorphous manganese dioxide nanoparticles for high-load electrodes. Another purpose of the present invention is to propose the application of amorphous manganese dioxide nanoparticles in electrode active materials, solving the problem of how to improve the conductivity of electrode active materials. The third purpose of the present invention is to propose a supercapacitor, solving the problem of how to improve the electrochemical performance of the capacitor.
[0007] Technical solution: The method for preparing amorphous manganese dioxide nanoparticles of the present invention comprises the following steps:
[0008] (1) Cool the potassium permanganate aqueous solution to a temperature not exceeding 4°C;
[0009] (2) adding ethanol to the cooled potassium permanganate aqueous solution, stirring and reacting at a temperature not exceeding 4° C. to obtain a first product;
[0010] (3) The first product is centrifuged to obtain a precipitate, which is then dried to obtain amorphous manganese dioxide nanoparticles.
[0011] Preferably, in step (1), the concentration of the potassium permanganate aqueous solution is 0.005-0.015M.
[0012] Preferably, in step (2), the volume ratio of ethanol to potassium permanganate aqueous solution is 1-2:2-4; and the stirring reaction time is at least 30 minutes.
[0013] Preferably, in steps (1) and (2), the method of not exceeding 4°C is an ice bath; in step (3), the drying method is: washing the precipitate alternately with deionized water and ethanol and then drying at 60-100°C for at least 8 hours.
[0014] The second aspect of the present invention discloses the use of amorphous manganese dioxide nanoparticles prepared by the above preparation method in electrode active materials.
[0015] Preferably, the electrode active material comprises the amorphous manganese dioxide nanoparticles, conductive carbon black and carbon nanotubes.
[0016] Furthermore, the mass ratio of the amorphous manganese dioxide nanoparticles, the conductive carbon black and the carbon nanotubes is 75-85:10-17:5-10.
[0017] The third aspect of the present invention discloses a supercapacitor, comprising an anode, a cathode and an electrolyte, wherein the cathode comprises the above-mentioned electrode active material; and the material of the anode comprises activated porous carbon, conductive carbon black and carbon nanotubes.
[0018] Preferably, the loading amount of amorphous manganese dioxide nanoparticles in the cathode is 10-15 mg·cm -2 The loading amount of activated porous carbon in the anode is 20-25 mg cm -2 .
[0019] Preferably, the electrolyte is a Na2SO4 aqueous solution.
[0020] In some embodiments, the concentration of the Na2SO4 aqueous solution is 0.5-3M, preferably 0.5-1M.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0022] The present invention provides a high-load MnO2 electrode, which uses amorphous MnO2 composed of MnO2 nanoparticles as an energy storage material and provides a higher MnO6 exposure ratio. By mixing conductive carbon black (CCB) and carbon nanotubes (CNTs) with MnO2 nanoparticles, the conductivity of the active material is fully improved, sufficient conductive paths are provided, and high capacitance is generated at high MnO2 mass loading. The maximum mass loading of MnO2 / CCB / CNTs on the electrode can be increased to 26.8 mg cm -2 , the capacitance is 196.3F·g -1 . With an optimized mass loading of 13.5 mg cm -2 The electrode exhibited 371.3 F·g based on the weight of MnO2. -1 Due to the excellent electrochemical properties of the MnO2 / CCB / CNTs mixture, the high-load asymmetric capacitor made of amorphous MnO2 and activated porous carbon (APC) has an ultra-high capacitance of 780.3 μWh·cm -2 Ultra-high areal energy density and 34.3W·h·kg -1 The asymmetric supercapacitor also exhibits excellent cycling stability (over 98.2%, 8000 cycles). These combined results meet the requirements of high-load energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of bulk manganese dioxide, porous manganese dioxide and nano-sized manganese dioxide for high loading electrode;
[0024] Figure 2 The test results of amorphous manganese dioxide nanoparticles; (a)-(c) are scanning electron microscope images; (d)-(e) are transmission electron microscope images; (f) is selected area electron diffraction (SAED); (g) is X-ray diffraction spectrum (0℃ and 25℃); (h) is pore size distribution (BJH model); (i) is X-ray photoelectron spectroscopy (Mn 2p);
[0025] Figure 3 is a scanning electron microscope image of amorphous manganese dioxide nanoparticles;
[0026] Figure 4 The transmission electron microscope image and size distribution statistical diagram of amorphous manganese dioxide nanoparticles; wherein (a) is a transmission electron microscope image; (b) is a size distribution of amorphous manganese dioxide nanoparticles;
[0027] Figure 5 is the cumulative pore volume of amorphous manganese dioxide nanoparticles;
[0028] Figure 6 It is the full spectrum of X-ray photoelectron spectrum of amorphous manganese dioxide nanoparticles;
[0029] Figure 7 The figures are the test results of the electrochemical properties of amorphous manganese dioxide electrodes; (a) is a schematic diagram of the conductive path of manganese dioxide / carbon nanotube / carbon black composite electrode materials; (b) is a diagram showing the change in specific capacitance of amorphous manganese dioxide nanoparticles containing carbon black; (c) is a diagram showing the specific capacitance of amorphous manganese dioxide / carbon black composite materials containing carbon nanotubes; (d) is a diagram showing the change in weight specific capacitance and surface specific capacitance under mass loading; (e) is a diagram showing the cyclic voltammetry curve of manganese dioxide / carbon black / carbon nanotube electrodes at different scan rates; (f) is a diagram showing the constant current charge and discharge curve of manganese dioxide / carbon black / carbon nanotube electrodes at different current densities; (g) is a diagram showing the change in weight specific capacitance and coulomb efficiency of manganese dioxide / carbon black / carbon nanotube electrodes with current density;
[0030] Figure 8 The performance test results of the electrode; wherein (a) is the constant current charge and discharge curve of the amorphous manganese dioxide electrode with different carbon black contents; (b) is the rate performance of the amorphous manganese dioxide / carbon black electrode with different carbon nanotube contents;
[0031] Fig. 9 At 50mV·s -1 Cyclic voltammetry curves of amorphous manganese dioxide / carbon black / carbon nanotubes with different mass loadings at a scan rate of ;
[0032] Fig.10 At 10mV·s -1 Cyclic voltammetry curves of amorphous manganese dioxide / carbon black / carbon nanotube electrode and activated carbon powder / carbon black / carbon nanotube electrode at a scan rate of ;
[0033] Fig.11 The electrochemical performance test results of asymmetric supercapacitors assembled from amorphous manganese dioxide / carbon black / carbon nanotubes and activated carbon powder / carbon black / carbon nanotubes; (a) shows the cyclic voltammetry curves recorded at different potential windows (20 mV·s -1 ); (b) shows the cyclic voltammetry curve (1.8 V, 5 to 100 mV·s -1 ); (c) shows the constant current charge and discharge curve (0.5 to 10A·g -1 ); (d) shows the rate performance; (e) shows the Ragone plot; (f) shows the cycle stability (4.0 A·g -1 ); (g) The figure shows the LED lighting time of two asymmetric supercapacitors;
[0034] Fig.12The electrochemical performance test results of an asymmetric supercapacitor assembled from amorphous manganese dioxide / carbon black / carbon nanotubes and activated carbon powder (APC); (a) is a Ragone plot; (b) shows the change in energy density with mass loading. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0036] Example 1: A method for preparing amorphous manganese dioxide nanoparticles is as follows:
[0037] The raw materials used in the preparation process are potassium permanganate (KMnO4, ≥99.5%, Sinopharm Group), sodium sulfate (Na2SO4, 99.0%, Aladdin), polyvinylidene fluoride (PVDF, ≥99%, Mw≈534000 g·mol -1 , Aladdin), ethanol (99.5%, Aladdin), potassium chloride (KCl, 99.8%, Shanghai Chemical Reagent Co., Ltd.), N-methylpyrrolidone (NMP, 99.9%, Aladdin), conductive carbon black (CCB, super conductive carbon black, Aladdin), agar powder (95.5%, Sigma-Aldrich), activated porous carbon (APC) (specific surface area: 2000m 2 ·g -1 , Aladdin).
[0038] (1) Place 40 mL of 0.01 M potassium permanganate aqueous solution in an ice bath with stirring for 30 minutes;
[0039] (2) directly adding 20 mL of ethanol to the cooled potassium permanganate solution, and placing the solution in an ice bath for 60 min under stirring to obtain the first product;
[0040] (3) The first product is centrifuged to obtain a precipitate, the precipitate is washed alternately with deionized water and ethanol, and dried at 80° C. for 12 hours to obtain amorphous manganese dioxide nanoparticles.
[0041] like Figure 1 As shown, in order to achieve a high loading of manganese dioxide electrode, the ineffective mass in the electrode should be very low, because the ineffective mass occupies a high weight and volume content, but contributes little to the capacitance of the electrode. The active material utilization (γ) can be expressed as:
[0042] γ=m AM / (m AM +m DM )
[0043] Among them, m AM is the active mass, m DMis the inactive mass. For MnO2 electrodes, due to their low conductivity, only a very thin layer (1-2 nm) is available for energy storage, and most of the bulk mass is inactive. Therefore, the calculated capacitance of bulk MnO2 electrodes is always below 50 F·g -1 . This capacitance decreases almost linearly inversely with the mass loading of manganese dioxide on the electrode, since the added manganese dioxide is almost completely inactivated. Based on this, a pore-forming strategy was adopted to activate bulk manganese dioxide by increasing the contact surface between manganese dioxide and electrolyte ions. It is certain that the ineffective mass content in porous manganese dioxide is significantly reduced due to the presence of continuously distributed and interconnected pores, which not only provides a considerable surface area for electrochemical reactions but also provides rich ion transport paths. However, porous manganese dioxide electrodes often suffer from poor rate performance due to the poor ion transport caused by the high micropore content. In addition, due to the limitations of pore-forming engineering, a large amount of ineffective manganese dioxide is still present in the electrode. Therefore, when the mass loading is lower than 1.0 mg cm -2 When the capacitance is high, porous manganese dioxide electrodes can achieve high capacitance, but this cannot meet the requirements of high energy density devices.
[0044] To avoid the above defects, manganese dioxide for high-loading electrodes should be designed with a nano-sized structure, which ensures a high content of active materials and contributes to its high specific surface area. Specifically, the content of exposed MnO6 units in nano-sized manganese dioxide is increased, which directly promotes capacitance. In addition, well-distributed nano-sized manganese dioxide can provide a hierarchical pore structure with micropores, mesopores and macropores coexisting in the electrode, which provides a smooth ion transport path and ensures good rate performance.
[0045] The morphology of manganese dioxide nanoparticles was studied by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 3 As shown in Figure (a), the manganese dioxide prepared in this example is a compact substance with a block structure, which can be attributed to the agglomeration of manganese dioxide nanoparticles during the drying stage. Figure 2 As shown in Figure (a), this block structure is not completely compact without any gaps. Under high magnification, a porous structure composed of interconnected nanoparticles can be observed, which ensures the high density and high porosity of manganese dioxide, resulting in high capacitance and high electrolyte ion transport efficiency in a certain volume of space (such as Figure 2 (b) Figure and Figure 3 As shown in Figure (b) of the figure). Therefore, this porous structure is considered to be an ideal electrochemically active material for high-loading electrodes. The average diameter of these nanoparticles was calculated to be 36.6 nm, providing abundant exposed MnO6 units for electrochemical reactions (such as Figure 4In addition, the irregular shapes of these nanoparticles result in an increased specific surface area, providing abundant electrochemically active sites (e.g. Figure 2 It is worth noting that no obvious lattice fringes can be observed from the high-resolution transmission electron microscopy image, indicating that the crystallinity of the manganese dioxide nanoparticles is low (as shown in Figure (c)). Figure 2 (d) in the middle), which means a high content of lattice defects. Figure 2 The low crystallinity of manganese dioxide nanoparticles can also be confirmed as shown in Figures (e) and (f). The unclear diffraction rings indicate that the manganese dioxide nanoparticles with amorphous characteristics have poor crystallinity. In addition, no obvious diffraction peaks were detected in the X-ray diffraction pattern, further indicating the amorphous characteristics of manganese dioxide nanoparticles. The structure with a large number of crystal defects produces a high specific surface area (366m 2 ·g -1 ) and hierarchical pore structure and high pore volume (e.g. Figure 2 Figure (g), Figure (h) and Figure 5 The chemical composition information and valence state of the amorphous manganese dioxide nanoparticle structure were explored by X-ray photoelectron spectroscopy (XPS). Figure 6 In the high-resolution Mn2p XPS spectrum, two main peaks corresponding to Mn2p3 / 2 (642.8 eV) and Mn2p1 / 2 (654.5 eV) can be observed, with a spin energy difference of 11.7 eV, indicating a manganese dioxide phase. 2+ , Mn 3+ and Mn 4+ The average oxidation state of manganese in amorphous manganese dioxide nanoparticles was calculated to be 3.61, indicating that the enhanced electrochemical reaction between amorphous manganese dioxide and electrolyte ions (such as Figure 2 (as shown in Figure (i)).
[0046] Based on the above results, ultrafine amorphous manganese dioxide nanoparticles with high specific surface area and interconnected pores show that the exposed MnO6 units increase, which significantly improves the electrochemical performance. Therefore, the obtained structure is considered to achieve enhanced specific capacitance when the mass loading is low. However, with the increase of the mass loading of amorphous manganese dioxide nanoparticles, the capacitance is severely attenuated, which is attributed to the poor electrical conductivity leading to inefficient charge / ion transfer. Specifically, the charge generated by the electrochemical reaction of the amorphous manganese dioxide nanoparticles close to the current collector can be transferred in time. However, due to the unreasonable pore distribution, amorphous manganese dioxide nanoparticles often lack electrolyte ions. And the amorphous manganese dioxide far away from the current collector is almost the opposite. Therefore, conductive additives (CCB) are usually applied to improve conductivity. In theory, the content of CCB should be high enough to ensure sufficient contact between CCB nanoparticles, thereby providing a smooth charge transfer path. However, when calculated based on the total weight of active materials and conductive additives that occupy a certain mass but provide little capacitance, the specific capacitance may be very low. Therefore, a three-dimensional conductive network should be designed to assist charge transfer and reduce the content of CCB (e.g. Figure 7 (as shown in Figure (a)).
[0047] Example 2: A method for preparing an electrode active material is as follows:
[0048] MnO2 / CCB / CNTs composites were prepared by a mixing method. First, amorphous manganese dioxide was mixed with CCB in a certain mass ratio to form a MnO2 / CCB mixture. To achieve high wettability of the mixture, carbon nanotubes were stirred in a mixed solution of 0.1M hydrochloric acid and 0.1M nitric acid at 80°C for 6 hours, then washed with deionized water for more than 10 times under ultrasonic dispersion, and stored in ethanol to form 1.0 mg mL -1 Afterwards, the dispersion was added to a MnO2 / CCB mixture dispersion (10 mg / mL in ethanol) under ultrasound for 60 minutes and then dried at 60°C for 8 hours.
[0049] In order to determine the optimal content of conductive carbon black (CCB), a series of electrodes (such as Figure 8 As shown in Figure (a). Figure 7As shown in Figure (b), the weight specific capacitance calculated based on the weight of pure amorphous manganese dioxide nanoparticles increases sharply in the initial stage and then stabilizes with the increase of CCB content, which is attributed to the enhanced electrochemical reaction with the increase of conductive additives. The optimal CCB content is calculated to be about 14.6% based on the specific capacitance of the mixture of amorphous manganese dioxide nanoparticles and CCB, which experiences an upward stage and then a decay stage with the increase of CCB content. This can be attributed to the low weight specific capacitance of CCB. Note that when the scan rate increases from 2 to 100 mV·s -1 When , only 36% of the initial capacitance is retained, which means that the charge transfer path in the electrode is blocked (such as Figure 7 In order to improve the electrochemical response rate of the high-load amorphous manganese dioxide electrode, a certain amount of carbon nanotubes (CNTs) was added to the manganese dioxide / conductive carbon black (MnO2 / CCB) mixture (amorphous manganese dioxide: 85.4wt%, conductive carbon black: 14.6wt%), as shown in Figure (c). Figure 8 As shown in Figure (b), at a high scan rate (100mV·s -1 ), a significant improvement in capacitance retention can be observed, indicating the presence of an interconnected three-dimensional conductive network. However, the capacitance increase calculated based on the mass of pure amorphous manganese dioxide nanoparticles was not significant (2 mV·s -1 ). Therefore, after the introduction of CCB, the electrochemical performance at low scan rate or low current density was fully exploited. However, with the increase of scan rate or current density, the capacitance was severely attenuated, which was significantly improved by the application of CNTs. Therefore, the reasonable CNTs content was determined to be 7.4%, which ensured that when the scan rate increased from 2 to 50 mV·s -1 Based on these results, the optimal contents of amorphous manganese dioxide nanoparticles, conductive carbon black and carbon nanotubes were determined to be 79.1 wt %, 13.5 wt % and 7.4 wt %, respectively.
[0050] Figure 7 Figure (d) and Fig. 9 The fluctuations of specific capacitance and areal capacitance with mass loading are shown. Obviously, the gravimetric specific capacitance decays severely with increasing mass loading, which can be attributed to the fact that the gravimetric capacitance decreases significantly when the mass loading exceeds 15 mg cm -2When the amorphous manganese dioxide nanoparticles are loaded, the connection between the amorphous manganese dioxide nanoparticles and the current collector is poor. Specifically, for high-load electrodes, it can be estimated that the invalid mass content in the amorphous manganese dioxide electrode increases significantly, which is due to the obstruction of the charge transfer path between the excess amorphous manganese dioxide nanoparticles and the current collector. Therefore, the area capacitance increases almost proportionally to the mass loading in the initial stage and then rises slowly. In other words, the area capacitance is not always proportional to the mass loading. There is still a gap between the ideal area capacitance and the actual value, especially for high-load electrodes (>15mg·cm -2 Therefore, a reasonable mass loading of 10.0 to 15.0 mg cm -2 Based on these results, a high-load amorphous manganese dioxide electrode (3.5 mg cm -2 ).like Figure 7 As shown in Figure (e), a rectangular cyclic voltammetry curve was obtained, indicating a fast electrochemical response between amorphous manganese dioxide nanoparticles and electrolyte ions. Specifically, the electrolyte can be smoothly transferred to the surface of amorphous manganese dioxide nanoparticles, and the generated charge can be transferred to the current collector in a timely manner, resulting in a fast electrochemical response. Therefore, the discharge branch is almost symmetrical with its charging branch, indicating a reversible electrochemical reaction. According to the triangular shape of the constant current charge-discharge curve, the capacitance calculated based on the weight of the amorphous manganese dioxide nanoparticles is 371.3F g -1 The capacitance calculated based on the total weight of amorphous manganese dioxide nanoparticles, conductive carbon black and carbon nanotubes is 293.3 F g -1 Achieved over 60% capacity retention (0.25 to 20 A g -1 ), which means that the high loading electrode has good electrochemical performance. In addition, the Coulombic efficiency remains above 98% at all current densities, further demonstrating the high reversibility of the prepared electrode (e.g. Figure 7 (f) and (g) in the figure).
[0051] Embodiment 3: A supercapacitor, which is composed as follows:
[0052] In 1.0M Na2SO4 solution, an asymmetric supercapacitor was assembled with MnO2 / CCB / CNTs as cathode and APC / CCB / CNTs as anode. MnO2 represents the amorphous manganese dioxide nanoparticles prepared in Example 1, and MnO2 / CCB / CNTs represents the electrode active material prepared in Example 2, which is composed of amorphous manganese dioxide nanoparticles, conductive carbon black and carbon nanotubes with mass percentages of 79.1%, 13.5% and 7.4%, respectively.
[0053] In a typical preparation process, polyvinylidene fluoride (PVDF) was dissolved in N-methyl-2-pyrrolidone (NMP) to form a homogeneous solution (50 mg / mL). Then, the PVDF / NMP solution was added to the pre-prepared MnO2 / CCB / CNTs mixture at a mass ratio of 90:10 to form a slurry, which was coated on the surface of nickel foam. After that, the coated electrode was placed in a vacuum oven at 120°C overnight to remove the solvent and moisture. Finally, the prepared electrode was pressed in a uniaxial direction at 10 MPa for 30 seconds. The loading on the electrode ranged from 1.0 to 28.0 mg·cm -2 The negative electrode was prepared in the same manner by replacing the amorphous manganese dioxide with APC.
[0054] The capacitance is 176.6 F·g based on the total weight of APC, CCB and CNTs. -1 The mass loadings of the cathode and anode were 12.6 and 22.4 mg cm -2 .like Fig.10 As shown, at 20mV·s -1 At a scan rate of , the amorphous MnO2 nanoparticles and APC obtained two rectangular shapes, indicating that they have ideal capacitive properties. Fig.11 Figure (a) shows the cyclic voltammetry curves of the amorphous MnO2 / CCB / CNTs / / APC / CCB / CNTs asymmetric device in the working voltage range from 0-1.0V to 0-2.0V. Obviously, all the cyclic voltammetry curves are close to a rectangular shape, indicating a good match between the anode and the cathode. Considering the cyclic performance of the device, the working potential window is set to 0-1.8V based on the electron charge ratio of the discharge process and the charging process, and the S value exceeds 0.9. Therefore, cyclic voltammetry tests were performed at different scan rates at a voltage of 0-1.8V (such as Fig.11 Note that the cyclic voltammetry curve of the prepared device is nearly rectangular, indicating that it has ideal capacitance characteristics. -1 The rectangular shape can be retained even at a scan rate of 1.5 Å, which means that the prepared device has excellent rate performance, which can be attributed to the optimized CCB and CNTs contents. In addition, a shape close to a triangle was observed for the constant current charge-discharge curve, indicating that there is a satisfactory configuration between the MnO2 / CCB / CNTs electrode and the APC / CCB / CNTs electrode (e.g. Fig.11 Based on the total weight of amorphous MnO2, APC, CCB and CNTs, at 0.5A·g -1 At a current density of 1.34 W, the gravimetric specific capacitance is estimated to be 76.2 F·g -1In addition, according to the area of the electrode, the area capacitance of the asymmetric supercapacitor is 1.73F·cm -2 The high capacitance is attributed to the fact that the amorphous MnO2 nanoparticles provide abundant exposed MnO6 units for electrochemical reactions. In addition, when the current density increases from 0.5 to 20 A·g -1 When the initial capacitance is 2.5 W, about 54% of the initial capacitance is still retained, indicating that the asymmetric supercapacitor has excellent rate performance (such as Fig.11 (as shown in Figure (d)).
[0055] The Ragone diagram of an asymmetric device is shown in Fig.11 Figure (e) and Fig.12 As shown in Figure (a). Obviously, when the power density is 0.45kW·kg -1 34.3W·h·kg -1 The maximum gravimetric energy density of 780.3 μWh cm -2 The excellent areal energy density of 2.5 Å / cm2 / CNTs is higher than that of most high-load supercapacitors. The observed excellent capacitive performance is attributed to the high exposed MnO6 ratio and the synergistic effect of the MnO2 / CCB / CNTs electrode and the APC / CCB / CNTs electrode. For comparison, a series of asymmetric capacitors were prepared and Fig.12 Figure (b) shows the change of maximum gravimetric energy density under different mass loadings. Obviously, with the increase of mass loading, at 0.45 W kg -1 A slight decrease in energy density was observed at a power density of 1.37 W, indicating the high uniformity of the electrode material. This can be attributed to the highly porous structure of the prepared nanostructure consisting of interconnected amorphous MnO2 nanoparticles. Specifically, at low current density, the electrolyte ions can transfer to the surface of amorphous MnO2 nanoparticles and fully undergo electrochemical reactions. However, as the mass loading increases from 2.5 to 16.3 mg cm -2 (positive electrode), the surface energy density dropped from 21.3 to 14.6 W·h·kg -1 , which is attributed to the smooth charge transfer path. In addition, after 8000 cycles (5.0 A·g -1 ), which can be attributed to the optimized working potential window and the high electrochemical stability of amorphous MnO2 (e.g. Fig.11 (f)). It is worth noting that the Coulombic efficiency (>99.5%) remains almost unchanged, further demonstrating the high stability of the prepared asymmetric supercapacitor. Finally, a red LED was successfully lit up by two assembled asymmetric supercapacitors (as shown in Figure 2). Fig.11The results show that asymmetric supercapacitors with high-loading electrodes can meet the needs of practical energy storage devices.
[0056] Embodiment 4: The rest is the same as Embodiment 1, except that:
[0057] In step (1), the concentration of the potassium permanganate aqueous solution is 0.005M.
[0058] In step (2), the volume ratio of ethanol to potassium permanganate aqueous solution is 2:3; and the stirring reaction time is 30 minutes.
[0059] In step (3), the precipitate is washed and then dried at 60° C. for 14 h.
[0060] Embodiment 5: The rest is the same as Embodiment 1, except that:
[0061] In step (1), the concentration of the potassium permanganate aqueous solution is 0.015M.
[0062] In step (2), the volume ratio of ethanol to potassium permanganate aqueous solution is 1:4; and the stirring reaction time is 45 minutes.
[0063] In step (3), the precipitate is washed and dried at 100°C for 8 hours. The present invention proposes a simple, controllable and cost-effective strategy to prepare amorphous MnO2 nanostructures composed of ultrafine MnO2 nanoparticles for high-load electrodes. The optimal contents of amorphous MnO2, CCB and CNTs were determined to be 79.1%, 13.5% and 7.4%, respectively. Based on the weight of pure amorphous MnO2, at 13.5 mg cm -2 371.3F·g was obtained under a mass loading of -1 The high capacitance is attributed to the abundant exposed MnO6 units produced by ultrafine nanoparticles. The high-loading asymmetric supercapacitor assembled from amorphous MnO2 and activated porous carbon provides 780.3 μWh cm -2 The surface energy density and 34.3W·h·kg -1 The prepared asymmetric supercapacitor exhibits excellent cycling stability after 8000 cycles, retaining more than 98% of the initial capacitance. In principle, the amorphous MnO2 prepared in the present invention is emphasized to be applicable to high-load electrodes.
Claims
1. A method for preparing amorphous manganese dioxide nanoparticles, characterized in that: The steps include: (1) Cool the potassium permanganate aqueous solution to a temperature not exceeding 4°C; (2) adding ethanol to the cooled potassium permanganate aqueous solution, stirring and reacting at a temperature not exceeding 4° C. to obtain a first product; (3) The first product is centrifuged to obtain a precipitate, which is then dried to obtain amorphous manganese dioxide nanoparticles.
2. The method for preparing amorphous manganese dioxide nanoparticles according to claim 1, characterized in that: In step (1), the concentration of the potassium permanganate aqueous solution is 0.005-0.015M.
3. The method for preparing amorphous manganese dioxide nanoparticles according to claim 1, characterized in that: In step (2), the volume ratio of ethanol to potassium permanganate aqueous solution is 1-2:2-4; and the stirring reaction time is at least 30 minutes.
4. The method for preparing amorphous manganese dioxide nanoparticles according to claim 1, characterized in that: In steps (1) and (2), the method of not exceeding 4°C is an ice bath; in step (3), the drying method is: washing the precipitate alternately with deionized water and ethanol and then drying at 60-100°C for at least 8 hours.
5. Use of the amorphous manganese dioxide nanoparticles prepared according to the preparation method according to any one of claims 1 to 4 in electrode active materials.
6. The use according to claim 5, characterized in that: The electrode active material comprises the amorphous manganese dioxide nanoparticles, conductive carbon black and carbon nanotubes.
7. The use according to claim 6, characterized in that: The mass ratio of the amorphous manganese dioxide nanoparticles, the conductive carbon black and the carbon nanotubes is 75-85:10-17:5-10.
8. A supercapacitor, characterized in that: The invention comprises an anode, a cathode and an electrolyte, wherein the cathode comprises the electrode active material as claimed in claim 6; and the material of the anode comprises activated porous carbon, conductive carbon black and carbon nanotubes.
9. The supercapacitor according to claim 8, characterized in that: The loading amount of amorphous manganese dioxide nanoparticles in the cathode is 10-15 mg cm -2 The loading amount of activated porous carbon in the anode is 20-25 mg cm -2 .
10. The supercapacitor according to claim 8, characterized in that: The electrolyte is a Na2SO4 aqueous solution.
Citation Information
Cited By
Functionalized nanoparticles loaded with antiviral drugs, collagen-based hydrogel eye drops based on in-situ catalytic oxygen production and preparation method and application of collagen-based hydrogel eye drops
CN121570613A